Polymorphisms of pharmacogenetic candidate genes affect etomidate anesthesia susceptibility - Ma, Lulin; Huang, Yan; Huang, Shiqian; Xu, Feng; Wang, Yafeng; Zhao, Shuai; Deng, Daling; Ding, Yuanyuan; Zhang, Tianhao; Zhao, Wenjing; Chen, Xiangdong (Frontiers in Genetics, 2022)
ABSTRACT: Purpose: Etomidate is widely used in general anesthesia and sedation, and significant individual differences were observed during anesthesia induction. This study aimed to explore the molecular mechanisms of different etomidate susceptibility at the genetic level. Methods: 128 patients were included in the study, the bispectral index (BIS), mean arterial pressure (MAP) and heart rate (HR) were recorded when the patients entered the operating room for 5 minutes, before the administration of etomidate, 30s, 60s, 90s, 120s and 150s after the administration of etomidate, and the corresponding single nucleotide polymorphisms (SNPs) were analyzed. Results: Significant individual differences were observed in etomidate anesthesia. The results of two-way ANOVA showed that CYP2C9 rs1559, GABRB2 rs2561, GABRA2 rs279858, GABRA2 rs279863 were associated with the BIS value during etomidate anesthesia; UGT1A9 rs11692021 was associated with the EOAA/S score during etomidate anesthesia; GABRB2 rs2561 was associated with MAP. Multiple linear stepwise regression model results showed that CYP2C9 rs1559, GABRA2 rs279858 and GABRB2 rs2561 were associated with the BIS value and UGT1A9 rs11692021 was associated with the EOAA/S; GABRB2 rs2561 was associated with MAP. Conclusion: GABRA2 rs279858, GABRB2 rs2561, CYP2C9 rs1559 and UGT1A9 rs11692021 are the SNPs with individual differences during etomidate anesthesia. Key word: single nucleotide polymorphisms (SNPs), etomidate, susceptibility, GABRA2, GABRB2, CYP2C9, UGT1A9.